Prevalence of risk factors for non-communicable diseases among adult population in district Amritsar of Punjab - Gill, Kanwal Preet Kaur; Devgun, Priyanka; Mahajan, Shyam Lal; Kaur, Harpreet (International Journal Of Community Medicine And Public Health, 2018)
Background: The burden of chronic non-communicable diseases (NCDs) is rising rapidly all over the world. World Health Organization recommends surveillance of risk factors in different countries so that appropriate intervention is implemented to cut down the morbidity and mortality from NCDs. Hence, the presented study was planned with the objective of assessing the prevalence of common modifiable risk factors for NCDs in district Amritsar of Punjab. Methods: The study was conducted in Urban Health Training Centre of Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar. Sample size of 400 was calculated by adopting WHO Stepwise approach to surveillance guidelines. Behavioural risk factors, physical measurements and biochemical measurements were studied. Data was collected, compiled and analyzed by using SPSS 19.0 for windows evaluation version. Results: Majority of study subjects (98.75%) were taking inadequate vegetable and fruit servings irrespective of their age, gender, place of residence and educational status. The prevalence of physical exercise was also very low with only 86 (21.5%) of study subjects doing minimum recommended physical exercise. Among men, 27% of them were drinking alcohol, but among women, there was only one. Prevalence of smoking was very low (1.5%). Nearly one third (30.7%) of study subjects were overweight, 13.3% were obese, 35.3% were hyperglycemic and 36.7% were hypertensive. The prevalence of all these risk factors was found to be higher in higher age group. Conclusions: Low physical activity coupled with poor fruits and vegetables intake and alcohol consumption along with high prevalence of obesity, diabetes and hypertension is worrisome and needs to be addressed effectively.